Plagiarism in academic writing in higher education institutions: A bibliometric analysis - Hadijah, Ahmad; Muhammad Ashraf, Fauzi (International Society for Technology, Education and Science (ISTES), 2024)
Higher education institutions (HEI) are increasingly challenged by plagiarism, which threatens their academic standards and integrity. This is due to the fact that students have access to an overwhelming amount of information online, making it easier for them to copy and paste without giving proper credit or attribution. Additionally, the prevalence of technology has made it easier to copy and paste without detection. The study aimed to analyze the trends in plagiarism in academic writing by using bibliometric analysis, which is a technique that can measure and analyze the use of published documents. This analysis was used to identify any potential changes in the prevalence of plagiarism in academic writing over time and to identify potential factors that could be influencing it. The data is extracted from Scopus database with Boolean and proximity search strategy and found 579 related journal articles. There are tabulations of results ranging from descriptive analysis, citation analysis, co-citation analysis, and co-word analysis. The descriptive findings revealed that 'academic integrity', despite not being included in the search string, was the most commonly occurring word with 284 indicating a significant relationship between plagiarism in academic writing in HEIs. In addition, citation analysis for the top ten documents was presented. The findings of co-citation analysis highlight factors, new trends of academic integrity, and mitigation plans against plagiarism, while co-word analysis are thematically presented in three prominent clusters which is academic misconduct study, ethics and academic integrity. In most prominent articles cited by many authors, contract cheating is the new trend of plagiarism. As a result, it sheds light on the fact that academic integrity issues go beyond a new phenomenon that needs to be taken seriously. This study has both theoretical and practical implications for minimizing future plagiarism risks as well as identifying and recommending potential solutions to the problem.